SISTEM PERSEDIAAN ALAT TULIS KANTOR SEBAGAI PENUNJANG PENGAMBILAN KEPUTUSAN BAGIAN LOGISTIK DI PERGURUAN TINGGI RAHARJA - Sri Rahayu; Tuti Nurhaeni; Malidah Rohmah (Universitas Raharja, 2015)
Utilization of a Computerized Information Systems in the universities is very important in this globalization era. With the existence of computerized information systems, processing allcritical data can be arranged neatly so as to facilitate the storage and retrieval of data. Website is one of the media information that is very effective in presenting information, including for the universities. Problems faced by the user on the stationery system at Perguruan Tinggi Raharja is the lack of support system that is able to facilitate the decision to supply stationery. Stationery system is still using semi-computerized system, there are many papers used are inefficient and not optimal in supporting the user to make a decision. This makes the process of data management to be slow, as well as when the supply of information when needed. The methodology used is through a process of interviews and observations to the user to analyze and implement the system. The results of the analysis is described by using the modeling language UML (Unified Modeling Language). Implementation of the final result achieved is the establishment ofa Webbased information systems that is connected to the database server that facilitates data management and generate information as a decision support for the user.